VDAC1-interacting molecules promote cell death in cancer organoids through mitochondrial-dependent metabolic interference - Stefano Conti Nibali; Silvia De Siervi; Enrico Luchinat; Andrea Magrì; Angela Messina; Lorenza Brocca; Stefania Mantovani; Barbara Oliviero; Mario U. Mondelli; Vito De Pinto; Cristian Turato; Cristina Arrigoni; et al. (2024)
The voltage-dependent anion-selective channel isoform 1 (VDAC1) is a pivotal component in cellular metabolism and apoptosis with a prominent role in many cancer types, offering a unique therapeutic intervention point. Through an